2019
DOI: 10.1177/2192568219850090
|View full text |Cite
|
Sign up to set email alerts
|

Do Clinical Outcomes and Sagittal Parameters Differ Between Diabetics and Nondiabetics for Degenerative Spondylolisthesis Undergoing Lumbar Fusion?

Abstract: Study Design: Retrospective cohort study. Objective: To assess the effect of diabetes mellitus (DM) on clinical and radiographic outcomes in patient with degenerative spondylolisthesis undergoing posterior lumbar spinal fusion. Methods: Analysis of patients who underwent open posterior lumbar spinal fusion from 2011 to 2018. Patients being medically treated for DM were identified and separated from nondiabetic patients. Visual analogue scale Back/Leg pain and Oswestry Disability Index (ODI) were collected, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Khan et al in contrast to our study observed no difference between the diabetic and nondiabetic groups in terms of clinical outcomes. Similarly, no difference was observed between the two groups in terms of the need for reoperation or postoperative complications [10] and a history of diabetes had no effect on exacerbation of poor prognosis. Oster et al reported that a history of diabetes or smoking did not affect the prognosis of surgery in these patients [11].…”
Section: Discussionmentioning
confidence: 87%
“…Khan et al in contrast to our study observed no difference between the diabetic and nondiabetic groups in terms of clinical outcomes. Similarly, no difference was observed between the two groups in terms of the need for reoperation or postoperative complications [10] and a history of diabetes had no effect on exacerbation of poor prognosis. Oster et al reported that a history of diabetes or smoking did not affect the prognosis of surgery in these patients [11].…”
Section: Discussionmentioning
confidence: 87%
“…However, results of studies on the risk factors for reoperation of DLS patients remain controversial. Rabah et al, have reported that diabetes was related to greater risk of reoperation [ 11 ], while Khan et al reported no significant association between diabetes and reoperation [ 12 ]. In the study performed by Zhong et al, obesity was found to be associated with a higher incidence of unplanned reoperations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%